Thiophene-thiosemicarbazone derivative (L10) exerts antifungal activity mediated by oxidative stress and apoptosis in C. albicans. (1st April 2020) - de Araújo Neto, Luiz Nascimento; de Lima, Maria do Carmo Alves; de Oliveira, Jamerson Ferreira; de Souza, Edson Rubhens; Feitosa Machado, Suellen Emilliany; de Souza Lima, Gláucia Manoella; Silva Buonafina, Maria Daniela; Brayner, Fábio André; Alves, Luiz Carlos; Sandes, Jana Messias; da Silva, Márcia Vanusa; de Castro, Maria Carolina Accioly Brelaz; et al.
Abstract: Reactive oxygen species (ROS) cause cell damage and death. To reverse these effects, cells produce substances such as reduced glutathione (GSH) that serve as substrates for antioxidant enzymes. One way to combat microbial resistance includes nullifying the effect of glutathione in microbial cells, causing them to die from oxidative stress. The compound 2-((5-nitrothiophen-2-yl)methylene)- N -(pyridin-3-yl) hydrazine carbothioamide (L10) is a new thiophene-thiosemicarbazone derivative with promising antifungal activity. The aim of this study was to evaluate its mechanism of action against Candida albicans using assays that evaluate its effects on redox balance. Treatment with L10 promoted significant changes in the minimum inhibitory concentration (MIC) values in ascorbic acid and GSH protection tests, the latter increasing up to 64-fold of the MIC. Using nuclear magnetic resonance, we demonstrated interaction of L10 and GSH. At concentrations of 4.0 and 8.0 μg/mL, significant changes were observed in ROS production and mitochondrial membrane potential. The cell death profile showed characteristics of initial apoptosis at inhibitory concentrations (4.0 μg/mL). Transmission electron microscopy data corroborated these results and indicated signs of apoptosis, damage to plasma and nuclear membranes, and to mitochondria. Taken together, these results suggest a possible mechanism of action for L10 antifungal activity, involving changes in cellular redox balance, ROS production, and apoptosis-compatible cellular changes. Graphical abstract: Image 1 Highlights: Thiophene-thiosemicarbazone derivative (L10) causes interference in the redox balance of Candida albicans . Thiophene-thiosemicarbazone derivative (L10) causes death by apoptosis in Candida albicans . L10 causes an increase in reactive oxygen species by binding to reduced glutathione in Candida albicans .